Learning models that can improve elementary school students' creative thinking ability - Febriarsita Eka Sasmita; Rendra Sakbana Kusuma (Jurnal Bidang Pendidikan Dasar, 2023)
There are several abilities that can accommodate students in facing the 21st century, one of which is the ability to think creatively, but based on educational report cards, students' ability to think creatively is low. This study aims to describe a learning model that can stimulate the emergence of creative thinking abilities of elementary school students through the literature study method. Based on the results of the research and discussion, the researchers concluded that increasing the ability to think creatively can be pursued through three types of learning models, including (1) problem-based learning models, (2) discovery-based learning models, and (3) project-based learning models. These learning models include problem-solving, problem-posing, problem-based learning, guided inquiry learning, discovery learning, and project-based learning. This learning model was chosen because it has been proven by many researchers and has syntactic relations and indicators of creative thinking ability